Osteopontin Has a Crucial Role in Osteoclast‐Like Multinucleated Giant Cell Formation. Issue 3 (March 2014) - Oh, Yukiko; Oh, Iekuni; Morimoto, Junko; Uede, Toshimitsu; Morimoto, Akira
ABSTRACT The osteoclast (OC) is a major player in the pathogenic bone destruction of inflammatory bone diseases such as rheumatoid arthritis and Langerhans cell histiocytosis. Recently, it was shown that immature dendritic cells (iDC) fuse faster and more efficiently than monocytes in forming OC‐like multinucleated giant cells (MGCs), and that osteopontin (OPN) is involved in the pathogenesis of inflammatory bone diseases. In this study, we hypothesized that OPN is a key factor for generation of OC‐like MGCs from iDCs. We used an in vitro culture system to differentiate iDCs, derived from monocytes obtained from the blood of healthy donors, into OC‐like MGCs. We evaluated OPN levels and expression of OPN receptors during the course of differentiation. OPN has an arginine‐glycine‐aspartic acid (RGD) motif, and protease cleavage reveals a SVVYGLR motif. The concentrations of both full‐length and cleaved forms of OPN increased during the course of OC‐like MGC formation. Expression of OPN RGD‐ and SVVYGLR‐recognizing receptors also increased at later stages. We analyzed whether blocking OPN binding to its receptors affected OC‐like MGC formation. Monocytes treated with OPN siRNA were able to differentiate into iDCs effectively; however, differentiation of these iDCs into OC‐like MGCs was significantly reduced. The formation of OC‐like MGCs was not significantly reduced by RGD synthetic peptide. By contrast, SVVYGLR synthetic peptide caused a significant reduction. These data suggest that the cleaved form of OPN plays a critical role in driving iDC differentiation into OC‐like MGCs in the early phase of differentiation, in an autocrine and/or paracrine fashion. J. Cell. Biochem. 115: 585–595, 2014. © 2013 Wiley Periodicals, Inc.